OP09 TIPS outcomes for refractory ascites: a single centre experience. (6th September 2011) - Macnaughtan, J; Hogan, B; Tritto, G; Mullan, M; Yu, D; Thorburn, D; O'Beirne, J; Jalan, R; Patch, D; Burroughs, A
Abstract : Introduction: Transjugular intrahepatic portosystemic shunt (TIPS) insertion is established as an important intervention in the management of refractory ascites. We conducted a retrospective analysis of a large series of patients undergoing TIPS insertion for this indication. Aim: The aims of this study were to describe the series of patients undergoing TIPS insertion for refractory ascites at the Royal Free Hospital particularly with regards to survival and procedural success. Method: A retrospective analysis of the Royal Free Hospital radiology database was conducted to identify all patients who underwent all TIPS procedures between January 1991 and January 2011. Patient records were used to subsequently identify those patients in whom refractory ascites was the principal indication for TIPS insertion and to characterise this patient cohort. Patients were excluded if hydrothorax was the primary indication for TIPS insertion. All patients underwent baseline EEG/echocardiography and cross sectional imaging as part of their pre-procedural work up. Patients were requiring regular paracentesis and were either diuretic insensitive or intolerant. Results: 1073 TIPS-related procedures were conducted at the Royal Free Hospital between January 1991 and January 2011. Of these, 159 patients underwent TIPS insertion for refractory ascites. Within this patients cohort, the underlying aetiology of cirrhosis was: alcohol 56.0% (89/159), hepatitis C 12.6% (20/159), cryptogenic 8.8%(14/159) and other causes 22.6% (36/159). 29% (46/159) of the patients were female, 71% (113/159) were male. The mean age at the time of TIPS insertion was 54.3 (±0.94) yrs. The mean pre-TIPS MELD score was 15.26 (±0.57) with a mean pre-TIPS EEG frequency of 7.51 Hz (±0.20). The mean post-procedural portal pressure gradient was 11.0 mm Hg (±0.57). Six month, 12 month and 2-year survival post-TIPS insertion was 78%, 50% and 50% respectively. At 6 months, 63% of patients had no or minimal ascites, 29% had moderate volume ascites and only 8% had persistent large volume ascites. At 12 months, 69% of patients had no or minimal ascites, 21% had moderate volume ascites and 10% had persistent ascites requiring paracentesis. Conclusion: In a carefully selected group of patients, TIPS is an effective intervention in the management of refractory ascites.